Emerging Insights into Targeted Therapy-Tolerant Persister Cells in Cancer - Cabanos, Heidie Frisco (Cancers (Basel), 2021)
SIMPLE SUMMARY: Acquired resistance to molecularly targeted therapies remains a major challenge in the treatment of cancer. It has been hypothesized that drug-tolerant (or “persister”) cells without bona fide resistance mechanisms may survive initial drug treatment and undergo further evolution over time to acquire resistance mechanisms leading to cancer relapse. In this review, we will discuss insights into mechanisms and vulnerabilities of these cells revealed by recent in vitro, in vivo, and clinical studies. ABSTRACT: Drug resistance is perhaps the greatest challenge in improving outcomes for cancer patients undergoing treatment with targeted therapies. It is becoming clear that “persisters,” a subpopulation of drug-tolerant cells found in cancer populations, play a critical role in the development of drug resistance. Persisters are able to maintain viability under therapy but are typically slow cycling or dormant. These cells do not harbor classic drug resistance driver alterations, and their partial resistance phenotype is transient and reversible upon removal of the drug. In the clinic, the persister state most closely corresponds to minimal residual disease from which relapse can occur if treatment is discontinued or if acquired drug resistance develops in response to continuous therapy. Thus, eliminating persister cells will be crucial to improve outcomes for cancer patients. Using lung cancer targeted therapies as a primary paradigm, this review will give an overview of the characteristics of drug-tolerant persister cells, mechanisms associated with drug tolerance, and potential therapeutic opportunities to target this persister cell population in tumors.